The mechanism of mindfulness meditation on pain by functional magnetic resonance imaging method - Yıldız, Yasemin; Kocahan, Sayad; Çelenlioğlu, Alp Eren; Özler, Mehmet (The European Research Journal, 2023)
Pain is a subjective feeling having sensory, cognitive and emotional components. Brain regions that cognitively and affectively contribute to pain sensation are the anterior cingulate cortex (ACC), insula, prefontal cortex (PFC) and the default mode network (DMN). Depression and anxiety may accompany pain and they may exaggerate the pain via cognitive and affective disturbance. As a complementary treatment of pain, mindfulness meditation which is a therapeutic technique may be described as “non-judgmental awareness of the present moment”. Mindfulness meditation aims to focus on the experiences of bodily sensations and breathing in a non-judgmental and accepting manner. The functional magnetic resonance imaging (fMRI) is one of the tools that can explain the mechanism of action of mindfulness meditation on pain intensity, pain unpleasantness and the cognitive and affective disorders which accompanying pain. This study compiles studies examining the mechanism of action of mindfulness meditation on pain and pain accompanying pain unpleasantness, depression, anxiety with fMRI.